Quantum Dot-Based Assay for Cu2+ Quantification in Bacterial Cell Culture - Monras-Charles, J (2014)
A simple and sensitive method for quantification of nanomolar copper with a detection limit of 1.2 × 10-10 M and a linear range from 10-9 to 10-8 M is reported. For the most useful analytical concentration of quantum dots, 1160 ?g/ml, a 1/Ksv value of 11 ?M Cu2+ was determined. The method is based on the interaction of Cu2+ with glutathione-capped CdTe quantum dots (CdTe-GSH QDs) synthesized by a simple and economic biomimetic method. Green CdTe-GSH QDs displayed the best performance in copper quantification when QDs of different sizes/colors were tested. Cu2+ quantification is highly selective given that no significant interference of QDs with 19 ions was observed. No significant effects on Cu2+ quantification were determined when different reaction matrices such as distilled water, tap water, and different bacterial growth media were tested. The method was used to determine copper uptake kinetics on Escherichia coli cultures. QD-based quantification of copper on bacterial supernatants was compared with atomic absorption spectroscopy as a means of confirming the accuracy of the reported method. The mechanism of Cu2+-mediated QD fluorescence quenching was associated with nanoparticle decomposition. © 2014 Elsevier Inc. All rights reserved.